Enzyme-assisted mineralization of calcium phosphate: exploring confinement for the design of highly crystalline nano-objects. Issue 18 (29th April 2020) - Colaço, E.; Lefèvre, D.; Maisonhaute, E.; Brouri, D.; Guibert, C.; Dupont-Gillain, C.; El Kirat, K.; Demoustier-Champagne, S.; Landoulsi, J.
Abstract : Calcium phosphate mineralization is initiated through heterogenous enzymatic catalysis, resulting in the formation of highly ordered anisotropic nanostructures. The mineral phase features are modulated by physicochemical factors and confinement. Abstract : In hard tissues of vertebrates, calcium phosphate (CaP) biomineralization is a fascinating process that combines specific physicochemical and biochemical reactions, resulting in the formation of extracellular matrices with elegant nanoarchitectures. Although several "biomimetic" strategies have been developed for the design of mineralized nanostructured biointerfaces, the control of the crystallization process remains complex. Herein, we report an innovative approach to overcome this challenge by generating, in situ, CaP precursors in a confined medium. For this purpose, we explore a combination of (i) the layer-by-layer assembly, (ii) the template-based method and (iii) the heterogeneous enzymatic catalysis. We show the possibility of embedding active alkaline phosphatase in a nanostructured multilayered film and inducing the nucleation and growth of CaP compounds under different conditions. Importantly, we demonstrate that the modulation of the crystal phase from spheroid-shaped amorphous CaP to crystalline platelet-shaped hydroxyapatite depends on the degree of confinement of active enzymes. This leads to the synthesis of highly anisotropic mineralized nanostructures that are mechanically stable and with controlled dimensions, composition and crystal phase. The present study provides a straightforward, yet powerful, way to design anisotropic nanostructured materials, including a self-supported framework, which may be used in broad biomedical applications.